Zwangsmedikation psychisch erkrankter Menschen im Justizvollzug: Situation in Deutschland und Empfehlungen für die Praxis - Fuß, Johannes (Nervenarzt, 2020)
BACKGROUND: Coercive medical measures always represent an encroachment on the patient’s basic right to physical integrity and right to self-determination. If a patient is imprisoned, his basic rights are already severely restricted, and the coercive measure must also take place in a correctional facility. This amounts to a special challenge for everyone involved—but especially for the psychiatrist in charge. OBJECTIVES AND METHODS: This article is aimed at describing the psychiatric care of people with mental disorders in prisons, explaining the legal requirements for compulsory medication and giving recommendations for suitable conditions. RESULTS AND CONCLUSIONS: In Germany, there is no legally regulated health-care solution for people with mental disorders in custody in accordance with the laws on the mentally ill of the German federal states (Psychisch-Kranken-Gesetze). Therefore, in the case of serious mental disorders, imprisoned patients cannot be regularly provided with inpatient psychiatric care. As a result, compulsory medication within the correctional system must be considered if the course of the mental disorder is unfavorable. Compulsory medication in the German prison system has a special position compared with compulsory medication in psychiatric clinics, as doctors in most federal states can prescribe such medication without judicial involvement. The state legislators should check whether a legal adjustment would be necessary or helpful here. As the circumstances (legal and care-related) for imprisoned patients differ greatly from those of patients in clinics, the general conditions for compulsory medication should be carefully considered. We recommend consulting ethical case counseling if the decision is made without judicial involvement, and moving imprisoned patients to a psychiatric or at least to a medical ward before the administration of compulsory medication.